2017
DOI: 10.1016/j.jgr.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Animal lectins: potential receptors for ginseng polysaccharides

Abstract: Panax ginseng Meyer, belonging to the genus Panax of the family Araliaceae, is known for its human immune system-related effects, such as immune-boosting effects. Ginseng polysaccharides (GPs) are the responsible ingredient of ginseng in immunomodulation, and are classified as acidic and neutral GPs. Although GPs participate in various immune reactions including the stimulation of immune cells and production of cytokines, the precise function of GPs together with its potential receptor(s) and their signal tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 89 publications
1
16
0
Order By: Relevance
“…Furthermore, polysaccharides stimulate the dendritic-cell-enhancing production of interferon-γ, thereby promoting the production of cytotoxic cells against tumors. The present study also reported that KRG polysaccharides enhance the phagocytic activity of macrophages, which was consistent with our analysis [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, polysaccharides stimulate the dendritic-cell-enhancing production of interferon-γ, thereby promoting the production of cytotoxic cells against tumors. The present study also reported that KRG polysaccharides enhance the phagocytic activity of macrophages, which was consistent with our analysis [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Different classes of plant polysaccharides including glucans, mannans, pectins, arabinogalactans, galactans, fructans and xylans have shown promising immunomodulatory activity in vitro and in vivo ( Ferreira et al., 2015 ). These compounds can bind to cell surface receptors such as Toll-like receptors (TLR) and C-type lectins on monocytes and macrophages triggering an innate immune response ( Ferreira et al., 2015 ; Schepetkin and Quinn, 2006 ; Loh et al., 2017 ). The induction of innate immune response leads to several coordinated processes such as production of reactive oxygen species (ROS) and proinflammatory cytokines, enhanced phagocytosis, chemokinesis and chemotaxis ( Schepetkin and Quinn, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acidic polysaccharides were identified next. They consist of a complex polymer chain of monosaccharides rich in l -arabinose, d -galactose, l -rhamnose, d -galacturonic acid, d -glucuronic acid, and d -galactosyl residue linked together through glycosidic bonds, resulting in complex macromolecular architectures [5]. Although the structures of acidic polysaccharides are not clearly understood, it is known that they regulate immune systems [5].…”
Section: Introductionmentioning
confidence: 99%